Magnitude of opportunistic diseases and their predictors among adult people living with HIV enrolled in care: national level cross sectional study, Ethiopia - Teklu Weldegebreal; Ismael Ahmed; Abiyou Muhiye; Shoandagne Belete; Alemayehu Bekele; Mirgissa Kaba (BMC, 2018)
Abstract Background Opportunistic diseases cause morbidity and mortality among human immunodeficiency virus (HIV) infected persons. There is dearth of evidence on the magnitude and predictors of opportunistic diseases among PLHIV in Ethiopia. This study was conducted to determine the magnitude and predictors of opportunistic diseases among adults enrolled in the national HIV/AIDS care and treatment services and generate information for program planning and medicine quantification in the country. Methods A health facility-based cross-sectional study was conducted. Probability proportional to size and random sampling methods were employed to select health facilities and medical records of adult HIV-infected patients respectively. A total of 7826 medical records were reviewed from 60 health facilities nationwide. Socio-demographic and clinical data including diagnosis of opportunistic diseases were collected from the medical records. Period prevalence of opportunistic diseases over one year period was determined. Bivariate and multivariate logistic regression was used to measure associations between independent variables and the dependent variable, occurrence of opportunistic diseases. Results Of the total of 7826 study participants, 3748 (47.9%) were from hospitals and 4078 were from health centers. The majority (61.8%) were female. The median age was 32 years with interquartile range (IQR) of 27-40. The median duration of stay in HIV care was 56 (IQR = 28-80) months; 7429 (94.9%) were on antiretroviral treatment. A total of 1665 cases of opportunistic diseases were recorded with an overall prevalence estimated at 21.3% (95% confidence interval (CI): 20.36, 22.18%). Skin diseases (4.1%), diarrhea (4.1%), bacterial pneumonia (3.6%), recurrent upper respiratory tract infections (3.1%) and tuberculosis (2.7%) were the leading opportunistic diseases. Isoniazid preventive therapy coverage among eligible patients was 24.8%. Persons with a CD4 count < 200 cells/mm3 [adjusted odds ratio (AOR) 1.80, 95% CI: 1.45, 2.23]; and who were bed ridden or ambulatory functional status [AOR (95% CI) = 3.19 (2.32, 4.39)] were independent predictors of diagnosis of opportunistic diseases. Conclusion Opportunistic diseases were found to be pervasive among HIV infected adults in Ethiopia. Proactive identification and management, and prevention of opportunistic diseases should be strengthened especially among females, ambulatory or bed-ridden, and patients with low CD4 cell count.